The Expanding Cognitive-Behavioural Therapy Treatment Umbrella for the Anxiety Disorders: Disorder-Specific and Transdiagnostic Approaches. (June 2014) - Rector, Neil A; Man, Vincent; Lerman, Bethany
Cognitive-behavioural therapy (CBT) is an empirically supported treatment for anxiety disorders. CBT treatments are based on disorder-specific protocols that have been developed to target individual anxiety disorders, despite that anxiety disorders frequently co-occur and are comorbid with depression. Given the high rates of diagnostic comorbidity, substantial overlap in dimensional symptom ratings, and extensive evidence that the mood and anxiety disorders share a common set of psychological and biological vulnerabilities, transdiagnostic CBT protocols have recently been developed to treat the commonalities among the mood and anxiety disorders. We conducted a selective review of empirical developments in the transdiagnostic CBT treatment of anxiety and depression (2008–2013). Preliminary evidence suggests that theoretically based transdiagnostic CBT approaches lead to large treatment effects on the primary anxiety disorder, considerable reduction of diagnostic comorbidity, and some preliminary effects regarding the impact on the putative, shared psychological mechanisms. However, the empirical literature remains tentative owing to relatively small samples, limited direct comparisons with disorder-specific CBT protocols, and the relative absence of the study of disorder-specific compared with shared mechanisms of action in treatment. We conclude with a treatment conceptualization of the new transdiagnostic interventions as complementary, rather than contradictory, to disorder-specific CBT.